Professional helping as negotiation in motion: social work as work on the move - Ferguson, Harry (Taylor & Francis, 2016)
The delivery of welfare and professional helping, such as in medicine, nursing and social work is largely treated as though it is achieved through static and immobile practices. Research has been dominated by a focus on the sedentary as studies have stayed rooted in places like hospitals and offices, failing to follow practitioners when they go out to see their service users in their communities and homes. This paper explores the mobile character of professional helping through a focus on social work by examining what its practices look like through the lens of movement based social science. The paper draws on empirical data from my mobile and sensory ethnography of child protection work, where I went along with social workers and interviewed them in the car and observed them on home visits to families. It is argued that attention to movement gets to the heart of what these practices are, as shown in the multiple meanings of car journeys, and how keeping children safe relies on worker’s capacities to move their bodies when in the home by walking, playing with and staying close to the child. Professional help goes on through what Jenson calls “negotiation in motion”. Fundamentally, social work is work on the move.